Determinants of Budget Absorption with Accountability as a Moderating Variable in the Islamic-Based Government of Southeast Aceh District - Gundahara; Eka Nurmalasari; Zulia Hanum (LPPM Universitas Terbuka, 2024)
The aim of this research is to examine and analyze the influence of budget participation and human resource competency on budget absorption moderated by accountability. The approach used in this research is an associative approach. The population in this study was all regional apparatus organizations (OPD) in Southeast Aceh district, totaling 33 OPDs. The sample in this study was taken from 3 people from each regional apparatus organization (OPD), consisting of the head of department or secretary, authorized budget user and head of program sub-division, so that the number of respondents was 99 people. Data collection techniques in this research used documentation studies and questionnaires. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that budget participation and human resource competency have a significant effect on budget absorption, accountability moderates the influence of budget participation and human resource competency on budget absorption in Southeast Aceh Regency.